When the forest dies: the response of forest soil fungi to a bark beetle-induced tree dieback - Stursová, Martina; Snajdr, Jaroslav; Cajthaml, Tomáš; Bárta, Jiří; Santrůčková, Hana; Baldrian, Petr (The ISME journal, 2014)
Coniferous forests cover extensive areas of the boreal and temperate zones. Owing to their primary production and C storage, they have an important role in the global carbon balance. Forest disturbances such as forest fires, windthrows or insect pest outbreaks have a substantial effect on the functioning of these ecosystems. Recent decades have seen an increase in the areas affected by disturbances in both North America and Europe, with indications that this increase is due to both local human activity and global climate change. Here we examine the structural and functional response of the litter and soil microbial community in a Picea abies forest to tree dieback following an invasion of the bark beetle Ips typographus, with a specific focus on the fungal community. The insect-induced disturbance rapidly and profoundly changed vegetation and nutrient availability by killing spruce trees so that the readily available root exudates were replaced by more recalcitrant, polymeric plant biomass components. Owing to the dramatic decrease in photosynthesis, the rate of decomposition processes in the ecosystem decreased as soon as the one-time litter input had been processed. The fungal community showed profound changes, including a decrease in biomass (2.5-fold in the litter and 12-fold in the soil) together with the disappearance of fungi symbiotic with tree roots and a relative increase in saprotrophic taxa. Within the latter group, successive changes reflected the changing availability of needle litter and woody debris. Bacterial biomass appeared to be either unaffected or increased after the disturbance, resulting in a substantial increase in the bacterial/fungal biomass ratio.
Keywords: půdní mikrobiologie; Picea; Animals; stromy; Forests; Fungi; brouci; smrk; zvířata; Trees; biomasa; Coleoptera; houby; Biomass; Soil Microbiology; lesy